2022
DOI: 10.1097/ccm.0000000000005393
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion-Associated Delirium in Children: No Difference Between Short Storage Versus Standard Issue RBCs

Abstract: OBJECTIVES: Primary objective is to determine if transfusion of short storage RBCs compared with standard issue RBCs reduced risk of delirium/coma in critically ill children. Secondary objective is to assess if RBC transfusion was independently associated with delirium/coma. DESIGN:This study was performed in two stages. First, we compared patients receiving either short storage or standard RBCs in a multi-institutional prospective randomized controlled trial. Then, we compared all transfused patients in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…In a retrospective study of adult cardiothoracic surgery patients, intra-operative platelet transfusion was independently associated with development of delirium [19]. This is also consistent with the RBC transfusion literature, where several studies showed a strong and independent association between RBC transfusion and the development of pediatric delirium [13,14]. Authors suggested a two-hit mechanism for this relationship: critically ill children had an ongoing inflammatory response due to their underlying illness, and the blood product transfusion then multiplied this pre-existing inflammatory response.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In a retrospective study of adult cardiothoracic surgery patients, intra-operative platelet transfusion was independently associated with development of delirium [19]. This is also consistent with the RBC transfusion literature, where several studies showed a strong and independent association between RBC transfusion and the development of pediatric delirium [13,14]. Authors suggested a two-hit mechanism for this relationship: critically ill children had an ongoing inflammatory response due to their underlying illness, and the blood product transfusion then multiplied this pre-existing inflammatory response.…”
Section: Discussionsupporting
confidence: 79%
“…A systematic review of the studies on adults suggests that platelet transfusion potentiates the body's pro-inflammatory processes [12]. Two recent studies called on a similar inflammation-based mechanism for the development of pediatric delirium and found that RBC transfusions were independently and temporally associated with delirium development [13,14]. Given the lack of current research surrounding platelet transfusion and delirium, it remains unknown whether platelet transfusions play a pathophysiologic role in the development of pediatric delirium.…”
Section: Introductionmentioning
confidence: 99%
“…These contradictory findings to our current understanding should be corroborated in subsequent large-scale studies. In addition, there are a number of other previously identified risk factors for delirium that were not included in this meta-analysis: presence of significant organ dysfunction (e.g., congenital heart disease, liver failure, neurological disease), the extent of systemic inflammation, the extent of malnutrition and the use of blood products (16, 17). Hence, there may be a need for serial updates of this systematic review and meta-analysis as future studies are published.…”
mentioning
confidence: 99%